Correlation of Marketing Mix toward Purchase Intention of Teh Roso in Surabaya and Sidoarjo - Zildjian Limanto (iBuss Management, 2021)
COVID-19 Pandemic creates more awareness of health for people all around the world, including Indonesia. This pandemic causes the born of new businesses that focus on healthy products, such as tea products Teh Roso is one of the healthy product from Indonesia that is focusing on serving tea product that are healthy, pure, and economical to their customer. There are several factor that give impact to purchase intention of a product. Therefore, in this research, Marketing Mix are used to find the correlation of purchase intention of Teh Roso. In this research, questionnaires are spreaded to 30 respondents that owns a restaurant or café in Surabaya or Sidoarjo. The result of this research shows that Marketing mix do have high correlation toward purchase intention with promotion variable that has the highest correlation to purchase intention. Keywords:Marketing Mix, Purchase Intention, Teh Roso.